Active power compensator for a DC voltage bus of a renewable source - Morfin, Onofre (2024)
Renewable energy sources generate intermittent electrical power due to weather conditions, such as variations in wind speed and solar radiation. The nature of renewable energy sources requires new techniques to maintain the quality of electrical service and efficient use of energy. One of these techniques uses a battery bank when a renewable energy source does not generate the power level contracted by the utility grid. This article proposes a power compensator consisting of a bidirectional DC converter located between the battery bank and the DC bus of a renewable source. This compensator has two operation modes: one to store the excessive power in a battery bank; the other to deliver power when power intermittency occurs. The validation of the proposed power compensator is made using a prototype where the DC voltage bus of a renewable energy source is emulated through a DC generator-motor set, which allows bidirectional power flow.